Tanshinone production could be increased by the expression of SmWRKY2 in Salvia miltiorrhiza hairy roots. (July 2019) - Deng, Changping; Hao, Xiaolong; Shi, Min; Fu, Rong; Wang, Yao; Zhang, Yi; Zhou, Wei; Feng, Yue; Makunga, Nokwanda P.; Kai, Guoyin
Highlights: Tanshinones produced in S.miltiorrhiza was widely used for the treatment of cardiovascular and cerebrovascular diseases. A transcription factor named SmWRKY2 of subgroup I of the WRKY family was isolated and functionally characterized. Transgenic SmWRKY2 hairy roots produced increased content of tanshinones by elevating expression of SmDXS2 and SmCPS . Dual-Luciferase assay showed that SmWRKY2 can positively regulate SmDXS2 and SmCPS expression. Y1H and EMSA assays showed that SmWRKY2 can only bind to the W-box located in the promotor region of SmCPS directly. Abstract: Tanshinones are the main bioactive diterpenes in Salvia miltiorrhiza Bunge, are widely used for treating cardiovascular and cerebrovascular diseases. However, the biosynthetic mechanisms of these compounds have not yet been fully explained. In this study, a transcription factor named SmWRKY2 was isolated and functionally characterized. Multiple sequence analysis indicated it was classified into subgroup I of the WRKY family. Expression pattern showed that SmWRKY2 was mainly expressed in the stem and leaf and was inducible by methyl jasmonate (MeJA) treatment. Subcellular localization showed that SmWRKY2 was localized in the nucleus. Overexpression of SmWRKY2 in S. miltiorrhiza hairy roots significantly increased the expression of SmDXS2 and SmCPS, resulting in increased accumulation of tanshinones and the highest total tanshinone content was detected in OE-SmWRKY2-1 line, which was 1.83 times of the control. Meanwhile, tanshinone production was slightly reduced in the antisense-SmWRKY2 line. Dual-Luciferase assay showed that SmWRKY2 can positively regulate SmDXS2 and SmCPS expression, However, Y1H and EMSA experiments indicate that SmWRKY2 only binds to the W-box of the SmCPS promoter. Our study shows that SmWRKY2 is a positive regulator of tanshinone biosynthesis by mainly activating SmCPS. This study thus sheds new light on the regulatory role of SmWRKY2 in tanshinone biosynthesis.